Highly stretchable and transparent conductive film made of Pt nanocoil web - Xu ZHAO (The Japan Society of Mechanical Engineers, 2017)
High electrical conductivity and high optical transparency are desired for transparent conductive films (TCFs). The currently used conducting material, indium tin oxide (ITO), is high cost owing to the lack of indium source. In addition, its brittleness has limited its applications in flexible electronic devices. Although the alternative materials, such as carbon nanotube and metallic nanowires, have been extensively studied, there are still some issues needed to be addressed for their practical uses. This research reports a highly stretchable TCF, which is made by transferring a Pt nanocoil (NC) web to a transparent silicone rubber membrane. The fabricated Pt TCF exhibited a high optical transmittance over 90% within visible region. The stretching behaviors of a single-layered freestanding Pt NC web and a Pt TCF were investigated and the fracture mechanism was discussed. As a result, the respective fracture strain of freestanding Pt NC web and Pt TCF was approximately 20% and 15%, both of which were higher than that of ITO film. The decreased fracture strain of Pt TCF was attributed to a possible reason as follows. Compared to the freestanding Pt NC web, the in-plane deformation of Pt NCs in the TCF was restricted by the substrate layer, and hence the Pt TCF fractured more easily than the freestanding Pt NC web.